A novel anatomical consideration on the exposed segment of the facial artery. Issue 2 (14th October 2019) - Lee, Ji‐Hyun; Lee, Kangwoo; Jung, Wonsug; Youn, Kwan‐Hyun; Hu, Kyung‐Seok; Tansatit, Tanvaa; Park, Hyun Jun; Kim, Hee‐Jin
Abstract : An understanding of the location and depth of the facial artery (FA) is essential in aesthetic surgery and various cosmetic procedures. The purpose of this study was to clarify the three‐dimensional (3D) topography of the exposed segment (ES) of the FA and to provide information to help minimize complications during clinical procedures. From 50 embalmed adult cadavers, the undissected and dissected hemifaces were scanned and reconstructed using the 3D scanner. Then the topographic location of the ES was identified and measured from the superimposed the 3D images. The ES was observed in 82% of the whole specimens. The exposure patterns of the ES were examined, and classified into three types: Type I, one site exposed pattern (74%); Type II, two sites exposed pattern (8%); and Type III, nonexposed pattern (18%). The extent of the ES was located at 2.2 mm above and 4.2 mm below the cheilion (Ch)—otobasion inferius line, and 20.0 to 25.2 mm from the Ch on the lateral aspect. In the frontal view, the average distance from the mid‐pupillary line to the ES was 7.1 mm, and from the lateral canthal line to the ES was 6.1 mm. The ES was 7.6 mm below the skin surface. The results of this study will help to provide safe guidelines for filler injections as well as selecting the safe regions in various clinical procedures. Clin. Anat. 33:257–264, 2020. © 2019 Wiley Periodicals, Inc.